Oral health in young soldiers - Ana Caridad López Vantour; Ana María Quinzán Luna; Leonardo Nuñez Antunez; Miriulbis Marrero Ponce; Rosario Macias Frómeta (Centro Provincial de Información de Ciencias Médicas, 2016)
An epidemiological, observational, descriptive and cross-sectional study was carried out   in the Recruitment commission of Santiago de Cuba municipality, during the first semester of 2015, with the aim of characterizing the oral health in young soldiers. The universe was constituted by 80 young soldiers aged 17-22 years and both sexes to whom a questionnaire with clinical and epidemiological variables was applied, as well as a survey to evaluate the knowledge level on oral health.  The information was processed by means of the Epi Info program and the percentage was used as summary measure. The male sex and the age group 21-22 years prevailed with a high prevalence of decays. It was concluded that these young soldiers presented low decays index, poor oral hygiene and scarce level of knowledge on the topic.